Durable and Recyclable Superhydrophobic Fabric and Mesh for Oil–Water Separation. Issue 1 (21st August 2017) - Bano, Shaher; Zulfiqar, Usama; Zaheer, Usama; Awais, Muhammad; Ahmad, Iftikhar; Subhani, Tayyab
Abstract : The authors report durable and recyclable nanocomposite superhydrophobic coatings on two different substrates of fabric and mesh as prepared by titania nanoparticles and polydimethysiloxane (PDMS). The felted wool fabric and the steel mesh are initially coated with a thin layer of PDMS, which is followed by the deposition of nanocomposite coating of titania nanoparticles embedded in PDMS. The dual surface modification of two kinds of substrates generates highly hydrophobic surface character, which is retained after durability performance as measured in ultrasonication, sand, and emery paper abrasion tests. Oil–water separation experiments are performed using water mixtures with four oils, that is, n‐hexane, toluene, kerosene, and diesel to ensure the industrial applications of prepared composite materials. Moreover, nanocomposite coatings are tested for several cycles of oil–water separation in harsh conditions such as hot water, sodium chloride, and hydrochloric acid. The adopted approach improves the separation performance by inducing durability of the prepared nanocomposite coatings along with introducing recyclable character. Abstract : Durable, recyclable, and superhydrophobic nanocomposite coatings are prepared on fabric and steel mesh. The coatings comprise titania nanoparticles and polydimethylsiloxane (PDMS). The substrates are initially coated with PDMS, followed by deposition of titania/PDMS nanocomposite coating. The resulting highly hydrophobic materials are utilized for the separation of oil–water mixtures.